(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the growing interest and attention to the use of pedagogical technologies in the educational process today, the study of each subject in primary education, which forms the basis of general secondary schools. The use of pedagogical technologies in the teaching process provides methodological recommendations on how to create the basis for deep learning of students.